Analisis Yuridis Perjanjian Simpan Pinjam pada Koperasi Graha Arta Prima - Ayu Praditha, Azzahra; Amir, Diana; Syelvita, Rema (Zaaken: Journal of Civil and Business Law, 2025)
A savings and loan agreement is a relationship that often occurs between a savings and loan cooperative and its members. This agreement is the legal basis for the activity of borrowing and lending funds carried out by members to the cooperative. The savings and loan agreement between the savings and loan cooperative and its members is a legal relationship based on the principle of family and mutual trust between the cooperative and its members. The objectives of this study are: 1) to determine and analyze the rights and obligations between the Graha Arta Prima Cooperative and its members. 2) to determine and analyze the factors that influence the savings and loan agreement between the Graha Arta Prima Cooperative and its members. The method used in this study is an empirical legal approach by conducting direct interviews with the management and members of the cooperative. The results of this study are that there are still members of the Graha Arta Prima cooperative who are negligent in carrying out their obligations. This is based on several factors that affect the ability of members to carry out their obligations. These factors are external and internal factors experienced by members while involved in the savings and loan agreement in the Graha Arta Prima cooperative. The factor that is the biggest cause is the external factor in the form of economic conditions that often worsen. So that it affects debtors in carrying out their obligations.